PH‐Responsive Pillar[6]arene‐based Water‐Soluble Supramolecular Hexagonal Boxes. Issue 16 (14th March 2019) - Kaizerman‐Kane, Dana; Hadar, Maya; Tal, Noam; Dobrovetsky, Roman; Zafrani, Yossi; Cohen, Yoram
Abstract: We describe the preparation of the first water‐soluble pH‐responsive supramolecular hexagonal boxes (SHBs) based on multiple charge‐assisted hydrogen bonds between peramino‐pillar[6]arenes2 with the molecular "lid" mellitic acid (1 a ). The interaction between2 and1 a, as well as the other "lids" pyromellitic and trimesic acids (1 b and1 c, respecively) were studied by a combination of experimental and computational methods. Interestingly, the addition of1 a to the complexes of the protonated form of pillar[6]arene2, that is, 3, with bis‐sulfonate4 a or4 b, immediately led to guest escape along with the formation of closed1 a2 2 supramolecular boxes. Moreover, the process of the openning and closing of the supramolecular boxes along with threading and escaping of the guests, respectively, was found to be reversible and pH‐responsive. This study paves the way for the easy and modular preparation of different SHBs that may have myriad applications. Abstract : The first water soluble, pH‐responsive, supramolecular hexagonal boxes (SHBs) based on multiple charge‐assisted hydrogen bonds were prepared by simple addition of "lids" to the per‐diethyl‐amino‐pillar[6]arene2 . These supramolecular HBs can be obtained from simple components and in a modular way thus paving the way for the preparation of different pH‐responsive HBs that may have myriad applications.